Multidimensional Dakwah Era Cyberspace Pada Akun Youtobe Ma’had Aly Nurul Jadid - Nur Aisyah; Abu Khaer; Nur Miswatul Yulianti (Fakultas Agama Islam Universitas Billfath, 2022)
This research aims to analyze and master about the efforts tried by Ma' had Aly Nurul Jadid Paiton Probolinggo in building Multidimensional proselytizing cyberspace era through digital literacy to its academic community. This research uses a qualitative approach to phenomenological types, where researchers seek to master about entwined and growing phenomena. The method of gathering information is tried through participant observation, interview and documentation. Analysis of information is tried through the stages of presentation of information, reduction of information and withdrawal of conclusions. The results showed that digital literacy was tried by Ma' had Aly Nurul Jadid Paiton Probolinggo in building multidimensional proselytizing cyberspace era. Cyberspace is tried through Deployment of Digital Books, Discussion activities, Online Lectures Knolwedge Sharing of Virtual account. As well as Al-amiri's news paper